2020
DOI: 10.1038/s42003-020-0866-8
|View full text |Cite
|
Sign up to set email alerts
|

An abscisic acid-responsive protein interaction network for sucrose non-fermenting related kinase1 in abiotic stress response

Abstract: Yeast Snf1 (Sucrose non-fermenting1), mammalian AMPK (5′ AMP-activated protein kinase) and plant SnRK1 (Snf1-Related Kinase1) are conserved heterotrimeric kinase complexes that re-establish energy homeostasis following stress. The hormone abscisic acid (ABA) plays a crucial role in plant stress response. Activation of SnRK1 or ABA signaling results in overlapping transcriptional changes, suggesting these stress pathways share common targets. To investigate how SnRK1 and ABA interact during stress response in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…We have previously shown that AFP2 interacts with the SnRK1 catalytic subunits, SnRKα1 and SnRKα2, in Y2H and BiFC assays ( Carianopol et al, 2020 ). While transiently expressing AFP2 with the empty vector control in N. benthamiana , we observed that AFP2 induced CD in the infiltrated area of the leaf ( Figures 1A, B ; Supplemental Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that AFP2 interacts with the SnRK1 catalytic subunits, SnRKα1 and SnRKα2, in Y2H and BiFC assays ( Carianopol et al, 2020 ). While transiently expressing AFP2 with the empty vector control in N. benthamiana , we observed that AFP2 induced CD in the infiltrated area of the leaf ( Figures 1A, B ; Supplemental Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…AFP2 EAR did not activate the LacZ reporter and results with the leucine reporter were inconclusive, since there was similar yeast growth also with the negative control (empty vector) ( Figure 4A ). SnRK1α1 and α2 autoactivated when fused to the DBD ( Carianopol et al, 2020 ), therefore, reciprocal interactions could not be tested.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations